Authoritarian innovations and democratic reform in the "New Malaysia". Issue 6 (17th August 2020) - Dettman, Sebastian
ABSTRACT: Malaysia's National Front coalition, one of the world's most durable authoritarian governments, lost power in national elections held in 2018. Although incumbent turnover represents a significant step toward democratization, the reform of institutions and practices associated with political domination by the country's Malay Muslim majority has been slowed in the face of challenges from a new configuration of opposition forces. The new opposition, which includes UMNO, the former dominant party of the National Front, has framed democratic reforms initiated by the new government – and the more multiethnic ruling government itself – as a threat to the rights of the country's largest ethnoreligious community. In turn, the new government, seeking to defuse the opposition's electoral threat, and in part propelled to power by its commitment to preserve Malay Muslim political domination, has responded by maintaining non-democratic institutions and practices. The case highlights the extent to which the scope and scale of democratic reform are curbed not only by remnants of the former regime but also by newly elected governments seeking to maintain their position in power.